2006
DOI: 10.1097/01.blo.0000229335.36900.a0
|View full text |Cite
|
Sign up to set email alerts
|

The High Variability of Tibial Rotational Alignment in Total Knee Arthroplasty

Abstract: Although various techniques are advocated to establish tibial rotational alignment during total knee arthroplasty, it is unknown which is most repeatable. We evaluated the precision and accuracy of five tibial rotational alignment techniques to determine whether computer-assisted navigation systems can reduce variability of tibial component rotational alignment when compared to traditional instrumentation. Eleven orthopaedic surgeons used four computer-assisted techniques that required identification of anatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 26 publications
7
75
1
Order By: Relevance
“…Identical default positions with a 08 cut on the tibial plateau were used for CR and PS designs. Based on our previous studies, 11,14 femoral rotational alignment was varied between 158 external rotation and 158 internal rotation in 58 increments, and tibial rotational alignment for the CR implant was varied between 208 external rotation and 208 internal rotation in 58 increments. Due to its more highly constrained design, the simulation failed for the PS implant at the more extreme tibial rotational alignments.…”
Section: Journal Of Orthopaedic Research July 2011mentioning
confidence: 99%
See 2 more Smart Citations
“…Identical default positions with a 08 cut on the tibial plateau were used for CR and PS designs. Based on our previous studies, 11,14 femoral rotational alignment was varied between 158 external rotation and 158 internal rotation in 58 increments, and tibial rotational alignment for the CR implant was varied between 208 external rotation and 208 internal rotation in 58 increments. Due to its more highly constrained design, the simulation failed for the PS implant at the more extreme tibial rotational alignments.…”
Section: Journal Of Orthopaedic Research July 2011mentioning
confidence: 99%
“…[9][10][11] Siston et al 11 found rotational alignment errors ranging from 138 internal rotation to 168 external rotation. Errors can often occur in tibial component rotational alignment in the transverse plane, [12][13][14] ranging from 448 internal rotation to 468 external rotation. 14 The large variability may be due to the fact that small linear errors in identifying anatomic landmarks translate into large rotational errors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In total knee arthroplasty (TKA) the rotational alignment of the tibial component remains an unresolved problem [1]. The tibial component has been shown to have a wider range of rotation than the femoral one [2].…”
Section: Introductionmentioning
confidence: 99%
“…The tibial component has been shown to have a wider range of rotation than the femoral one [2]. Various techniques are used to ensure optimal alignment, but there is a lack of reliability and repeatability [1]. In a study of 109 TKAs, 50% were found to have tibial malrotation of more than 5 [3], which is sufficient to result in knee pain, a poor range of motion and instability [4,5].…”
Section: Introductionmentioning
confidence: 99%